From Ethnography to Cultural Anthropology: on the Issue of the Boundaries of Social Sciences in Armenia - Shagoyan, Gayane (History and Culture, 2025)
This article explores the ongoing disciplinary transition from ethnography to anthropology in post-Soviet Armenia—a process marked by considerable inconsistency and debate. The challenge of naming the discipline that studies the cultural characteristics of various groups emerged even during its initial development. Armenian intellectuals of the late 19th century participated in these discussions, often aligning with terminology and frameworks adopted in European academic traditions. However, the Soviet era imposed the term “ethnography” on the discipline in Armenia, a designation that has persisted into the post-Soviet period. This continuity has led to significant challenges both domestically and internationally.In global social sciences, “ethnography” is widely understood as a research method—primarily fieldwork—rather than a standalone discipline. Meanwhile, the discipline with similar content is better known as socio-cultural anthropology. This discrepancy complicates the external representation of Armenian academia and its institutional structure. Domestically, the term adds confusion, as it is often equated with the mission of preserving traditional culture, overshadowing its broader theoretical and methodological scope.The article aims to stimulate a critical discussion on the urgent need to reform and modernize the Armenian system of social sciences, including updating terminologies to align with international standards and accurately reflect the evolving content of the field.
Keywords: Armenian ethnography; Yervand Lalayan; cultural anthropology; ethnographic questionnaire; Soviet ethnography; culturology; cultural studies